KAIDAH FIKIH DALAM LEGITIMASI PUTUSAN DISPENSASI KAWIN: (KAJIAN PUTUSAN PENGADILAN AGAMA DI KALIMANTAN SELATAN) - Zaidah, yusna zaidah; Abdul Hamid; Erma Sauva Asvia (Institut Agama Islam Darul Ulum Kandangan, 2025)
Abstract:The principles of Islamic Jurisprudence are frequently employed by courts to legitimize marriage dispensation cases involving prospective brides and grooms who have not yet reached the legal minimum age for marriage, thereby allowing them to marry legally. This study is motivated by the perception that courts tend to readily approve such dispensations by referencing the principles of Islamic Jurisprudence as a primary legal consideration. Judges often cite